Controlling A Gas Plant Using State Space Approach - Yeo, DANIEL YEO REN WEI (Universiti Teknologi Petronas, 2009)
Monitoring and controlling of a plant’s process variables can be carried out using the computer via software in the instrumentation and control industry. Control systems oil and gas industries are designed using the conventional approach, as opposed to the modern control approach commonly used in aerospace industries, thus controller qualities such as robustness, optimality and adaptivity could have been overlooked. This project aims to theoretically apply the concepts of modern control engineering in plant process control systems. The entire project involves understanding process control and state space, grasping the concept of system identification and mastering the functions of MATLAB and Simulink for controller and observer design and simulation. Extensive utilization of MATLAB and Simulink were involved in the several experiments and simulations that were carried out and run. Results from this project indicate the practicality of modern control in plant process control systems. This project successfully achieved the theoretical implementation of modern control engineering in plant process control systems, paving way for a possible design of a new controller and observer strategy that are robust, optimal and adaptive via modern control approach.